Emotional stress, cortisol response, and cortisol rhythm in autism spectrum disorders: A systematic review. (October 2022) - van der Linden, Kim; Simons, Claudia; van Amelsvoort, Thérèse; Marcelis, Machteld
Abstract: Background: This systematic review evaluated whether there is evidence for (i) increased emotional stress levels, and (ii) a different biological stress response or rhythm [i.e., cortisol stress response, diurnal rhythm, or cortisol awakening response (CAR)] in individuals with autism spectrum disorder (ASD) relative to controls. Thirdly, the evidence for an association between emotional and biological stress in ASD was reviewed. Method: MEDLINE, Cochrane Library, and SAGE journals were searched until December 2020. In this review, there were no limitations regarding age, sex, or intelligence quotient. Studies were only reviewed if results were compared with controls without a developmental disorder. Only salivary cortisol was considered as biological stress measure. Results: Thirty-one studies were reviewed. Significantly higher self- and parent-reported emotional stress levels were found in individuals with ASD compared to controls. Regarding biological stress, the few studies in adults reported comparable cortisol stress responses and rhythms between both groups. In children/adolescents with ASD relative to controls, an increased, blunted, or similar cortisol stress response was reported, whereas the CAR did not differ in most studies, and diurnal rhythm was described as blunted or similar. Most studies found no significant association between parent-reported emotional stress and biological stress in ASD. Conclusions: Current findings suggest that heightened emotional stress is a clinically significant factor in ASD. To unravel the cortisol response and rhythm, research in specific subgroups within the ASD spectrum is warranted, aiming at a higher frequency of cortisol measurements, preferably combined with momentary emotional stress measurements. Highlights: Increased emotional stress levels in ASD show the need for stress management. No clear patterns were found in cortisol stress response and diurnal rhythm in ASD. Most studies found no association between emotional and biological stress in ASD. Future research in ASD spectrum subgroups is needed.